Development of Wordwall-Based Gamification on Question Exercises about French Cross-Cultural - Polili, Andi Wete; Ghofur, Abdul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to produce the development of Wordwall-based gamification media supported by Cross-cultural. The method used in this study is the Research and Development method with five phases of the ADDIE model according to Branch (2009), namely (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The application of wordwall-based gamification development was carried out as many as 4 materials that had an average pre-test score of 60.5% with a grade of "C (good enough)". And for the post test average value of 86.26% with grade "A (very good). While the assessment of the validator is divided into two, namely media assessment and material assessment. The assessment on 12 materials was declared in the Very Good category with an average value of 92.90%. As for the wordwall-based media assessment, the category is very good with an average value of 91.7%. From the application and assessment of the results of this study, it was found that the development of gamification of Wordwall-based French cross-cultural questions was declared effective.